Development of RP-HPLC methods for the analysis of melatonin alone and in combination with sleep-enhancing dietary supplements - Lily Peikova; Diana Tzankova; Maria Stancheva-Zlatkova; Alexander Zlatkov (Pensoft Publishers, 2024)
Melatonin, a hormone produced by the pineal gland, is widely recognized for its role in regulating sleep-wake cycles. With the increasing prevalence of sleep disorders, melatonin supplements have gained popularity as a natural remedy. Additionally, various sleep-enhancing dietary supplements combine melatonin with other active ingredients to enhance efficacy. Reliable and accurate analytical methods are essential for ensuring the quality, safety, and efficacy of these products. Reverse-phase high-performance liquid chromatography (RP-HPLC) is a powerful analytical technique widely used for the separation, identification, and quantification of compounds in complex mixtures. This article explores the development and validation of RP-HPLC methods for the analysis of melatonin, both as a single ingredient and in combination with other components in sleep-enhancing dietary supplements.